ANALYSIS OF WORKING MOTHER'S STATUS AND THE DEVELOPMENT OF PRESCHOOL AGE CHILDREN IN BENGKULU CITY: ANALYSIS OF WORKING MOTHER'S STATUS AND THE DEVELOPMENT OF PRESCHOOL AGE CHILDREN IN BENGKULU CITY - Febrianti, Tressia; hawara , Gian; Hapsari, Vike Dwi; Hasanah, Uswatun (STIKes Mitra Keluarga, 2024)
Introduction : Women are required to be mothers and help earn a living for the family. Working mother status can have both positive and negative impacts on family life. The role of mothers as primary caregivers is very influential in child development. This study aims to analyze the status of working mothers and the development of preschool children in Bengkulu City. Method: . This study used a quantitative research design with a descriptive correlation method through a cross sectional study approach. This study used 242 respondents who were mothers of pre-school children aged 48-72 months and were actively attending kindergarten education in Bengkulu City. Univariate analysis in this study was presented in categorical form and bivariate analysis using the chi-square test with a degree of significance sebesar 0.05. Result: The results of the analysis of the status of working mothers and the development of pre-school children in Bengkulu City show that out of 149 mothers who do not work have 102 children (68.5%) have age-appropriate development. From the results of the statistical tests conducted, a value of p = 0.017 < 0.05 was obtained. Conclusion: There is a relationship between the status of working mothers and the development of pre-school children in Bengkulu City. Working is an activity carried out to fulfill the mother's needs and improve family welfare. Working mothers should be able to increase interaction with children in their spare time to reduce the risk of developmental delays in childrens.